Human Rights Arrangement on Indonesian Law - S Masribut Sardol (Universitas Muhammadiyah Sidoarjo, 2014)
Article 1 paragraph (3) of the Constitution of 1945 (UUD 1945) stated that Indonesia is a Rule of Law. One feature of the Rule of Law is the existence of human rights in the state administration. Indonesia, since independence on August 17, 1945 has asserted the defense of human rights as stated in the opening clause and in the torso of the 1945 Constitution Article 27-34. In the era of reform, on the Government of President Habibie, the President and the Parliament ratified the UN convention against torture and other cruel, inhuman, or degrading human dignity into Law number 5 of 1998. Then the MPR also publishes the statutes of MPR No. XVII/MPR/1998 on Human Rights, which was followed up with the appearance of Law No. 39 of 1999 on human rights. In accordance with the law in Indonesia based on the sort of Law No. 12 of 2011, the actual products that have been issued by the Government (the MPR, DPR and President) that follow up the substance of Human Rights in the Constitution with established Assembly and the law is already correct. But when the MPR then does the second amendment to the Constitution on August 18, 2000 by adding a special article chapters and contains about Human Rights (as mentioned in Chapter X-A section 28 A-J), have made the complexity hierarchy of law in Indonesia because it is not in accordance with the substance of article 7 of Law No. 12 of 2011.